Determination of input-output energy and economic analysis of lavender production in Turkey - Gökdoğan, Osman (International Journal of Agricultural and Biological Engineering, 2016)
This research aims to perform an energy input-output analysis of lavender plant production in Isparta Province of Turkey. In order to determine the energy use efficiency of lavender plant, experiments and trials have been conducted on 10 lavender farms around Keçiborlu region of Isparta Province. Keçiborlu region of Isparta Province is an important location for lavender production. On these 10 lavender farms, energy input-output has also been calculated through trial and measurement methods during the production season of 2013. In lavender production, energy input has been calculated as 6336.50 MJ/hm2 and energy output has been calculated as 17 528.81 MJ/hm2. Energy inputs consist of chemical fertilizers energy by 52.88%, diesel energy by 33.32%, machinery energy by 9.72%, human labour energy by 2.85% and chemicals by 1.23%. Energy use efficiency, energy productivity, specific energy and net energy in lavender production have been calculated as 2.77; 0.75 kg/MJ, 1.34 MJ/kg and 11 192.31 MJ/hm2, respectively. Benefit-cost ratio has been calculated as 3.41 by dividing the gross value of production by the total cost of production per hectare. Keywords: output/input ratio, energy, specific energy, lavender, Turkey DOI: 10.3965/j.ijabe.20160903.1774 Citation: Gökdoğan O. Determination of input-output energy and economic analysis of Lavender production in Turkey. Int J Agric & Biol Eng, 2016; 9(3): 154－161.